Characteristics of flow distribution in central-type compact parallel flow heat exchangers with modified inlet and header. (5th February 2020) - Zhou, Jian; Ding, Ming; Bian, Haozhi; Zhang, Yinxing; Sun, Zhongning
Highlights: This study investigate flow distribution in central-type manifolds. Four methods have been applied to the modification of header and inlet. The modification can both reduce the pressure drop and flow maldistribution. The flow uniformity coefficient can be reduced by 66.36%. The pressure drop can be reduced by 36.03%. Abstract: This study numerically investigated the effect of the application of modified methods in a central-type parallel central-type heat exchanger on the flow distribution. For the flow maldistribution in the heat exchanger, it can greatly reduce the device performance. Therefore, It is significant to apply methods to the modification of the heat exchanger geometry for a better flow distribution. Except for the reducing the flow maldistribution, the reduction of the pressure drop in the heat exchanger should also be taken into account especially in the passive system such as passive containment cooling system and passive core cooling system etc., which are driven by natural circulation flow. Taken both flow maldistribution and pressure drop into consideration, four different methods have been applied in this study for a better flow distribution and less pressure drop. The methods include modifications of double-inlet and header. Besides, the inlet diameter and the insert angle and inlet have been investigated. The simulation results show that the modified double-inlet can reduce the flow maldistribution by 66.36% at most and pressure drop by 29.62% at the mean time. The modified header is able to reduce flow maldistribution by 53.16% at most and pressure drop by 36.03% meanwhile.